Telocytes contribute to aging-related modifications in the prostate - Sanches, Bruno Domingos Azevedo; Tamarindo, Guilherme Henrique; dos Santos Maldarine, Juliana; da Silva, Alana Della Torre [UNESP]; dos Santos, Vitória Alário [UNESP]; Lima, Maria Letícia Duarte [UNESP]; Rahal, Paula [UNESP]; Góes, Rejane Maira [UNESP]; Taboga, Sebastião Roberto [UNESP]; Felisbino, Sérgio Luis [UNESP]; Carvalho, Hernandes F. (Springer Nature, 2020)
Telocytes are interstitial cells present in the stroma of several organs, including the prostate. There is evidence that these cells are present during prostate alveologenesis, in which these cells play a relevant role, but there is no information about the presence of and possible changes in telocytes during prostate aging. Throughout aging, the prostate undergoes several spontaneous changes in the stroma that are pro-pathogenic. Our study used histochemistry, 3D reconstructions, ultrastructure and immunofluorescence to compare the adult prostate with the senile prostate of the Mongolian gerbil, in order to investigate possible changes in telocytes with senescence and a possible role for these cells in the age-associated alterations. It was found that the layers of perialveolar smooth muscle become thinner as the prostatic alveoli become more dilated during aging, and that telocytes form a network that involves smooth muscle cells, which could possibly indicate a role for telocytes in maintaining the integrity of perialveolar smooth muscles. On the other hand, with senescence, VEGF+ telocytes are seen in stroma possibly contributing to angiogenesis, together with TNFR1+ telocytes, which are associated with a pro-inflammatory microenvironment in the prostate. Together, these data indicate that telocytes are important both in understanding the aging-related changes that are seen in the prostate and also in the search for new therapeutic targets for pathologies whose frequency increases with age.